2013
DOI: 10.1099/jmm.0.068064-0
|View full text |Cite
|
Sign up to set email alerts
|

Administration of kefir-fermented milk protects mice against Giardia intestinalis infection

Abstract: Giardiasis, caused by the protozoan Giardia intestinalis, is one of the most common intestinal diseases worldwide and constitutes an important problem for the public health systems of various countries. Kefir is a probiotic drink obtained by fermenting milk with 'kefir grains', which consist mainly of bacteria and yeasts that coexist in a complex symbiotic association. In this work, we studied the ability of kefir to protect mice from G. intestinalis infection, and characterized the host immune response to thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 40 publications
3
25
0
3
Order By: Relevance
“…F. nucleatum is known to cause colon cancer by adhering to the colon epithelium and causing cell mutation. L. kefiri, L. kefiranofaciens and L. kefirgranum, which were proven by recent studies to have strong probiotic properties and positive health effects, are only present in kefir grains [14,15,16,17,18]. Moreover, the Saccharomyces and Kluyveromyces yeast strains unique to kefir grains also have important probiotic properties and antimicrobial effects that were observed in recent studies [19,20,21].…”
Section: Resultsmentioning
confidence: 96%
“…F. nucleatum is known to cause colon cancer by adhering to the colon epithelium and causing cell mutation. L. kefiri, L. kefiranofaciens and L. kefirgranum, which were proven by recent studies to have strong probiotic properties and positive health effects, are only present in kefir grains [14,15,16,17,18]. Moreover, the Saccharomyces and Kluyveromyces yeast strains unique to kefir grains also have important probiotic properties and antimicrobial effects that were observed in recent studies [19,20,21].…”
Section: Resultsmentioning
confidence: 96%
“…Medrano, Racedo, Rolny, Abraham, and Pérez (2011) demonstrated that orally administrated kefiran can alter the balance of immune cells in a murine model and increase the number of IgA + cells. In another study, the addition of kefir caused a reduction in the level of Giardia intestinalis infection 7 days post-infection (Franco et al, 2013). Kakisu, Abraham, Pérez, and De Antoni (2007) observed that kefir grains have an inhibitory effect on the growth and spore germination of B. cereus.…”
Section: Nutritional Characteristicsmentioning
confidence: 99%
“…Além disso, alguns micro-organismos isolados dos grãos têm a capacidade de se ligarem a células mutagênicas diminuindo o crescimento de um possível tumor. O consumo regular da bebida mostrou ser capaz de estimular células do sistema imunológico inato do intestino promovendo respostas mediadas por células contra tumores e infecções, auxiliando na homeostase intestinal e, além disso, apresentou atuação positiva sobre a pressão arterial devido a capacidade de dois peptídeos, presentes na bebida Kefir, em inibir a ECA -Enzima Conversora de Angiotensina (GUZEL-SEYDIM et al, 2011;FRANCO, et al, 2013;CARASI et al, 2014;NIELSEN et al, 2014;AHMED et al, 2015;PRADO et al, 2015).…”
Section: Introductionunclassified